PERFORMANCE OF SOMATIC EMBRYOGENESIS DEVELOPMENT UNDER DIFFERENT 2,4-D AND COCONUT WATER CONCENTRATION IN SUGARCANE VAR. BULULAWANG - Dewanti, Parawita; Maryam, Safira Arikha; Widuri, Laily Ilman; Okviandari, Purnama (BIOVALENTIA: Biological Research Journal, 2020)
Mass propagation technology through somatic embryogenesis has become an alternative for producing sugarcane seedlings rapidly.Application of proper plant growth regulator and concentration contribute to support somatic embryogenesis development. This study applied the combination of liquid and solid culture during proliferation stage to promote cell dispersion of embryogenic callus, rapid embryo somatic production, and improve regeneration potency of somatic embryo. Application of 2,4-D and coconut water during proliferation may expected as proper combination for accelerating somatic embryo development and regeneration.Development of somatic embryogenesis in sugarcane var. Bululawang during proliferation were described in this study. Embryogenic callusfrom induction media were transferred to proliferation media containing MS Basal + vitamin supplemented with sucrose different level of 2,4-D (1 mgl-1, 2 mgl-1, 3 mgl-1, 4 mgl-1 ) and coconut water (0% and 5%).Result showed that low concentration of 2,4-D induced optimum somatic embryogenesis development in proliferation and regeneration. Concentration of single 2,4-D 1 mgl-1 without coconut water induced rapid development of scutelar and coleoptilarduring proliferation and resulted in better shoot regeneration. In other way, 4 mgl-1 of 2,4-D concentration affected to inhibit scutelar and coloeptilar formed as the result of failure callus differentiation.